ANALISIS TEORI SOSIOLOGI DALAM PERKEMBANGAN OLAHRAGA MODERN - Rafid Nur Alfarizi; Husnul Khotimah; Farros Garsyani Habibie; Wibisono Surya Azwan; Ismail Saleh Hasibuan; Magdalena Junita Hutagalung; Dennis Pablo Diaz Marbun; Muhammad Rifky Prastiyo; Yan Indra Siregar; Putra Arima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of modern sport is a social phenomenon that has a significant impact on people's lives. Sport not only functions as a physical activity to maintain health, but has also developed into a part of culture, education, economics, media, and politics. This study aims to analyze sociological theories in the development of modern sport and understand the social impacts it has on society. The research method used is qualitative research with a descriptive approach through library research. Data were obtained from books, scientific journals, articles, and various literature sources relevant to the sociology of sport. The results show that functionalism theory views sport as a means of social integration and the formation of sportsmanship values, while conflict theory explains the existence of social inequality, commercialization, and the struggle for interests in modern sport. Symbolic interactionism theory explains that sport is a means of forming social identity through symbols and social interaction, while feminism theory highlights the importance of gender equality in the world of sport. In addition, technological developments and mass media have significantly influenced the development of modern sport. The conclusion of the study shows that modern sport has both positive and negative impacts on society, so that balanced sports management is needed to maintain the values ​​of education, sportsmanship, and social justice.